2020
DOI: 10.1093/humrep/deaa136
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of storage time after vitrification on pregnancy and neonatal outcomes among 24 698 patients following the first embryo transfer cycles

Abstract: STUDY QUESTION To evaluate the impact of storage time after vitrification on embryo viability, pregnancy outcomes and neonatal outcomes. SUMMARY ANSWER The prolonged storage time of vitrified embryos negatively affected pregnancy outcomes, including biochemical pregnancy rate, clinical pregnancy and live birth rate; but did not influence neonatal outcomes. WHAT IS KNOWN ALREAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 41 publications
5
36
1
Order By: Relevance
“…However, using multivariable logistic regression analysis, Ueno et al found that only the time from insemination to vitrification correlated with survival rates but not the duration of cryostorage [4]. In contrast, a recently published study, which investigated the effect of the storage time of embryos on pregnancy outcomes in 24 698 patients following the first embryo transfer cycles, found the rates of implantation, clinical pregnancy, multiple pregnancy, and live births decreased with prolonged storage time, although no significant difference in survival rates was found between the different groups [24]. Although the sample Test for overall effect: Z = 1.10 (p = 0.27)…”
Section: Discussionmentioning
confidence: 95%
“…However, using multivariable logistic regression analysis, Ueno et al found that only the time from insemination to vitrification correlated with survival rates but not the duration of cryostorage [4]. In contrast, a recently published study, which investigated the effect of the storage time of embryos on pregnancy outcomes in 24 698 patients following the first embryo transfer cycles, found the rates of implantation, clinical pregnancy, multiple pregnancy, and live births decreased with prolonged storage time, although no significant difference in survival rates was found between the different groups [24]. Although the sample Test for overall effect: Z = 1.10 (p = 0.27)…”
Section: Discussionmentioning
confidence: 95%
“…A clinical pregnancy was defined as a positive serum β-hCG 14 days after transfer, and a gestational sac can be documented by ultrasound 28–35 days after transfer. The miscarriage rate was defined as the number of clinical pregnancy losses divided by the number of clinical pregnancies ( 23 ). There were 27 patients of vanishing twin syndrome (VTS) in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The same vitrification method was employed throughout the whole study period. There were 4 vitrification operators involved in the study, all of whom have been well trained to perform vitrification technically as described in our previous study ( 18 ).…”
Section: Methodsmentioning
confidence: 99%